Analysis of the chemical construction industry in Singapore - Sivarajah Nadarajah. (2011)
Although very large contract values have been awarded in recent years for chemical plant construction in Singapore, these projects are rarely included in discussions of construction in Singapore. This is probably due to the fact that the contractors primarily involved in this sector are foreign, and that many of these projects are carried out offshore and outof- sight. Yet the present condition of construction for chemical plants is dynamic and this is likely to continue for several years to come.